The Relationship Between Teacher Behavior and Preparedness in Facing Pre-Flood Disasters at SMP Negeri Kecamatan West Limboto - Arifin Umar; Pipin Yunus; Fillah Hardiyanto (PROMOTOR, 2024)
The Relationship between Teacher Behavior and Preparedness in Facing Pre-Disaster in SMP Negeri West Limboto District. Guided by PIPIN YUNUS as Chairman and as Member of HASLINDA DAMANSYAH. Preparedness is a critical phase in the disaster management series because this phase will determine independence, the success of emergency response, the level of suffering of victims, and the safety of victims' lives during disasters. The purpose of the study was to determine the relationship between teacher behavior and preparedness in facing pre-flood disasters in SMP Negeri Limboto Barat District. Quantitative research design using correlational design with cross-sectional approach. Sampling using purposive sampling techniques with the number of respondents as many as 30 respondents. Data collection techniques use questionnaire sheets and data obtained from schools. The results of this study found good teacher behavior with preparedness in facing the pre-flood disaster category very ready as many as 14 respondents, good teacher behavior with preparedness in facing the pre-flood disaster ready category as many as 6 respondents, teacher behavior enough with preparedness in facing the pre-flood disaster very ready category as many as 1 respondents and teacher behavior enough with preparedness in facing the pre-flood disaster ready category as many as 9 respondents.  The results of the statistical test using Chi-Square obtained a value p=0,002 of > indigo, then Ha was accepted and Ho was rejected, meaning that there is a relationship between teacher behavior and preparedness in facing pre-flood disasters in West Limboto District Public Junior High School. a=0,05